Exploring workability in an older working population: associations with cognitive functioning, sleep quality, and technostress - Fattori, Alice; Comotti, Anna; Barnini, Teresa; Di Tecco, Cristina; Laurino, Marco; Bufano, Pasquale; Ciocan, Catalina; Serra, Daniele; Ferrari, Luca; Bonzini, Matteo (Frontiers in Public Health, 2024)
OBJECTIVE This observational study investigates workability and its associations with cognitive functioning, sleep quality and technostress among an older working population, also shedding light on potential differences between two occupational categories with different work schedules.Workers aged over 50, employed in different working sectors (banking/finance, chemical and metal-mechanic industry) were administered a self-report questionnaire including Work Ability Index (WAI), cognitive tests (Stroop Color Task, Corsi Blocks, Digit Span), sleep quality questionnaires (Pittsburgh Sleep Quality Index-PSQI; Insomnia Severity Index-ISI; Ford Insomnia Response to Stress Test-FIRST) and technostress scale. Linear regression models evaluated associations among variables, interaction effects investigated potential moderators.RESULTS A total of 468 aged workers categorized as white (WCWs; N=289, 62%) or blue collars (BCWs; N=179, 38%) were enrolled; most BCWs (N=104; 58%) were night shift workers. WCWs reported higher workability, cognitive functioning, sleep quality and lower technostress (except for invasion and privacy subscales) than BCWs. Associations between cognitive functioning and workability were statistically significant only for BCWs (slopes equal to 0.2 (0.33), 0.8 (0.34), -0.02 (0.001) for Memory Span Corsi, Block Span Digit and Interference Speed respectively; additionally, sleep quality significantly moderated this association (p=0.007). Higher levels of technostress were associated with lower workability, and this relationship was stronger for BCWs.The aging of the workforce has important implications for occupational health and safety.Our findings suggest potential interventions and protective measures to promote older workers' wellbeing; blue-collar workers particularly should benefit from tailored intervention to sustain workability and prevent technostress, considering the role of healthy sleep habits promotion.